Compact 8-port Coupled-fed MIMO Antenna Array for Sub-6 GHz 5G Smartphone Terminals - Satyanarayana B.; Srivastava S.K.; Meshram M.K. (My University, 2025)
A promising compact 8-port MIMO antenna array is operating in the 3.5 GHz band (3.4-3.6 \mathrm{GHz}) is proposed for future 5G mobile terminals. The proposed MIMO antenna array is comprised of two symmetric four coupled-fed inverted-L antenna arrays located on the extended side frames of the smartphone body respectively. Each antenna radiator in the proposed MIMO array has a compact size of 9 \times 7 \mathrm{~mm}^{2}(0.105 \lambda \times 0.0817 \lambda), \lambda is a free-space wavelength at 3.5 GHz. The 8-Antenna MIMO array is easily implemented in an LTE-42 (3.4-3.6 \mathrm{GHz}) band using such two array building blocks. The results shows that, each antenna element can cover the designated LTE-42 5G band with a good reflection coefficient \left(S-{11}\right) is better than-6 dB. The isolation between the any two any two antennas is better than -17.5 \mathrm{~dB} without extra decoupling structure. The desirable antenna efficiencies of 76 %-83 % and peak gains of 2-5 dB are observed respectively. The calculated envelop correlation coefficient (ECC) and diversity gain (DG) is less than 0.05 and 10 respectively throughout the 3.4-3.6 \mathrm{GHz} operating band. Vital results obtained proposed 8-port MIMO antenna array is promising for 5G terminals. © 2021 IEEE.